Phthalic acid esters – A grave ecological hazard in Cochin estuary, India. (March 2020) - Ramzi, A.; Gireeshkumar, T.R.; Habeeb Rahman, K.; Balachandran, K.K.; Shameem, K.; Chacko, Jacob; Chandramohanakumar, N.
Abstract: Distribution and ecological risks of Phthalic acid esters (PAEs) are poorly studied in estuarine environments in India. An attempt is made to chart the sources and assess the ecological risk of six PAE congeners (∑6 PAEs), present in dissolved and particulate forms in a tropical ecosystem (Cochin Estuary, India). Terrestrial input, as attested by a clear seasonality with substantial enrichment during monsoon (2–28 μg/L and 31–1203 μg/g; dissolved and particulate PAEs respectively) and post-monsoon (1–7 μg/L and 7–321 μg/g; dissolved and particulate PAEs respectively), was identified as the primary source. DnBP (di-n-butyl phthalate) and DEHP (diethylhexyl phthalate) were found to be the dominant species except for dissolved PAEs at pre-monsoon season. Statistical analysis identified two major clusters, in the ∑6 PAEs, composed of medium to high molecular weight PAEs (derived from plastic products) and low molecular weight PAEs (derived from cosmetic products). Calculated Risk Quotient (RQ) indicated values indicated moderate to high ecological risk for DnBP and DEHP congeners is a grim pointer to their detrimental effects on human health through consumption of contaminated organisms. Although substantial enrichment of suspended matter gets flushed out of the estuary during monsoon, there is a net PAE accumulation in the estuary during post-monsoon following an increased sedimentary restitution. Data of PAEs generated herein raises a challenge for immediate enactment of statutory legislation to curb and regulate hazardous contamination of estuaries by phthalic acid esters. Highlights: This study provides baseline information on 6 PAEs in Cochin estuary, India. PAEs exhibited significant seasonal heterogeneity, monsoon > post-monsoon > pre-monsoon. PAEs were in the range 0.36–27.99 μg/L in the dissolved phase and 7–1203 μg/g in the particulate phase. DnBP and DEHP were the dominant species in both the dissolved and particulate forms. DnBP and DEHP levels exceeded permissible environmental limits.